KARAKTERISTIK FILSAFAT, ILMU DAN AGAMA DALAM ISLAM - Maulida, Rizky; Sudirman (Jurnal Tawadhu, 2024)
This research discusses the characteristics of philosophy, science and religion from an Islamic perspective. Islamic philosophy is unique because it integrates revelation and reason in achieving truth, in contrast to Greek philosophy which prioritizes pure rationality. One important aspect of Islamic philosophy is the concept of prophecy, which combines logical thinking with divine guidance. This shows that Islamic philosophy is not only oriented towards logic, but also places revelation as the main guide. Science in Islam is seen as a means to understand the signs of Allah's greatness in His creation and to enrich life in this world and the afterlife. Science is not only empirical, but also includes spiritual and ethical dimensions, which makes it different from secular science. Islam is the moral foundation and main goal in the search for knowledge and truth. The principle of monotheism acts as a foundation in uniting philosophy, science and religion, thereby producing harmony in the Muslim worldview. This research uses a qualitative method with a descriptive approach. Various literature is used to analyze the relationship and differences between philosophy, science and religion in Islam. The results show that these three elements complement each other, forming a comprehensive framework for life, where philosophy provides logic, science adds insight, and religion is the main direction.